2002
DOI: 10.1046/j.1365-2133.2002.04991.x
|View full text |Cite
|
Sign up to set email alerts
|

Is skin ageing in the elderly caused by sun exposure or smoking?

Abstract: Smoking is an important determinant of macroscopic skin ageing/wrinkling in older subjects. This evidence suggests that skin ageing does not clearly provide an objective measure of cumulative ultraviolet exposure, and caution should be exercised before it is used in this way. The association between smoking and wrinkling provides important information for potential use in education campaigns to reduce smoking prevalence among young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 22 publications
0
73
1
2
Order By: Relevance
“…[1][2][3][4][5][6][7] In this study we have shown that severe facial wrinkling (Daniell score >IV) is significantly associated with a lower mean FEV 1 and COPD. Indeed, more than 80% of smokers with facial wrinkling fulfilled the spirometric criteria for COPD.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] In this study we have shown that severe facial wrinkling (Daniell score >IV) is significantly associated with a lower mean FEV 1 and COPD. Indeed, more than 80% of smokers with facial wrinkling fulfilled the spirometric criteria for COPD.…”
Section: Discussionmentioning
confidence: 90%
“…Facial wrinkling in smokers may therefore be a biomarker of susceptibility to COPD. C igarette smoking is associated with facial wrinkling [1][2][3][4][5][6][7] that increases with the number of pack years smoked. 2 5 Smoking is also the major risk factor for the development of chronic obstructive pulmonary disease (COPD).…”
mentioning
confidence: 99%
“…In recent years, due to the observed increase in life expectancy in modern societies the interest in the subject of late adulthood has increased. Many publi cations on aging indicate genetical and physiological conditioning of this phenomenon, yet they do not ex clude the influence of general lifestyle frequently re sulting from the educational level [1][2][3]. In various re search on different aspects of aging, including the in fluence of external factors on the involutional changes, ambiguities which raise questions can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Leung & Harvey, 2002 N = 792; 60+ years old; Races not specified Cross-sectional study from a random sample of those listed on a registry of general practitioners' patients.…”
Section: Journal Of Smoking Cessationmentioning
confidence: 99%